Evaluation of the Indonesian student talent identification program - Ferdinandus, Moses Eleazar; Widiastuti, Widiastuti; Setiakarnawijaya, Yasep; Subandi, Oman Unju; Samsudin, Samsudin; Setiawan, Iwan; Taufik, Muhamad Syamsul (Indonesian Journal of Research in Physical Education, Sport, and Health, 2024)
Background: Identifying pediatric talent in sports presents significant challenges due to the complex interaction of physical, psychological, and developmental factors. Research shows that traditional talent identification methods often result in low levels of accuracy, complicating the selection process for young athletes. Talent identification programs need to be conducted and monitored regarding their success. Objective: The study aimed to evaluate the Indonesian Student Talent Identification Program in 2022. Methods: This research uses qualitative techniques with an evaluation approach using the Context model, Input, Process, and Product (CIPP). Data collection methods include questionnaires, interviews, document studies, and observations. There were 34 provinces, and the sample consisted of 4,500 student respondents representing each district and city by random sampling. Data analysis using frequency analysis description. Result: (1) Context Evaluation: It has a solid legal and policy basis, and the government's goals and objectives are good, but it still needs to be on target. (2) Input Evaluation: participants, organization, financing, and committee have yet to be well implemented and need to be improved by the development of student talent identification each year. (3) Process Evaluation: Sports match regulations must constantly be updated by the development of the Indonesian Student Identification Program in 2022; the implementation of matches still needs to be adequately maximized. (4) Product Evaluation: Increased community participation and interest in organizing national potential young athletes training centers every year, the role of the media in sports publication and promotion to the community is increasingly expanded, and the search for potential athletes from the community needs to be optimized. Conclusion: Based on the discussion, the process of the Indonesian Student Talent Identification Program mechanism in 2022 refers to the achievements obtained by students and athletes both at the national level.